2016
DOI: 10.1016/j.neubiorev.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and cognition: A systematic review of 111 studies

Abstract: Further investigations are warranted to clarify this relationship. Earlier detection of the elevated Hcy levels may be an effective intervention to prevent cognitive impairment and dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 164 publications
2
45
1
3
Order By: Relevance
“…Epidemiological studies have reported the association between high circulating Hcy levels and AD, while longitudinal observations have revealed that the influence of Hcy on AD is independent from other confounders17181920. However, conflicting results have also been published regarding this relationship2122.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have reported the association between high circulating Hcy levels and AD, while longitudinal observations have revealed that the influence of Hcy on AD is independent from other confounders17181920. However, conflicting results have also been published regarding this relationship2122.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our preliminary findings on Sulmedol on lowering Hcy levels in normal subjects, and in improving the neurobehavioral symptoms in moderateadvanced AD stage, raise the relevance of Sulmedol in targeting Hcy/ H 2 S link in development of novel AD therapeutics. Intervention trials using B-vitamin supplementation, however, have produced somewhat inconsistent findings on cognitive function [18][19][20][21][22]. In reviewing the plethora of many cross-sectional and prospective studies, increased levels of plasma total homocysteine are related to the severity of cognitive impairment and AD and vascular dementia.…”
Section: Discussionmentioning
confidence: 99%
“…By making use of a patented biotechnology for upscale manufacturing and quality control, the product has achieved a purity of 99.5% [18]. Pharmacokinetics data indicated that 10% to 40% of ingested sulfur is absorbed from the gastrointestinal tract as sulfides and excreted as sulfates in the urine.…”
Section: A Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…It is logical that riboflavin would have an impact on cognitive function because homocysteine (Hcy) metabolism and one-carbon metabolism rely on it. Any reduction in the activity of enzymes in these pathways due to insufficient riboflavin, or other B vitamins, results in high Hcy, metabolic disorders, and accelerated brain cell death and is associated with cognitive decline, Alzheimer's disease, and Parkinson's disease (94)(95)(96)(97)(98)(99).…”
Section: Riboflavinmentioning
confidence: 99%